Fluorescence Lifetime Imaging Microscopy (FLIM) of Intracellular Transport by Means of Doubly Labelled siRNA Architectures. (25th June 2021) - Doll, Larissa; Lackner, Jens; Rönicke, Franziska; Nienhaus, Gerd Ulrich; Wagenknecht, Hans‐Achim
Abstract: For monitoring the intracellular pathway of small interfering RNA (siRNA), both strands were labelled at internal positions by two ATTO dyes as an interstrand Förster resonance energy transfer pair. siRNA double strands show red emission and a short donor lifetime as readout, whereas siRNA antisense single strands show green emission and a long donor lifetime. This readout signals if GFP silencing can be expected (green) or not (red). We attached both dyes to three structurally different alkyne anchors by postsynthetic modifications. There is only a slight preference for the ribofuranoside anchors with the dyes at their 2'‐positions. For the first time, the delivery and fate of siRNA in live HeLa cells was tracked by fluorescence lifetime imaging microscopy (FLIM), which revealed a clear relationship between intracellular transport using different transfection methods and knockdown of GFP expression, which demonstrates the potential of our siRNA architectures as a tool for future development of effective siRNA. Abstract : siRNA traffic lights : RNA is labelled at internal positions of the sequence by two different fluorescent dyes that undergo interstrand energy transfer. The emission is shifted to green after processing of siRNA into single stranded antisense RNA, potentially binding to target mRNA. This allowed imaging of siRNA by microscopy, using the fluorescence lifetime of the donor dye.